Skin cancer concerns particular to women - Z. Al-Dujaili; M. Henry; A.S. Dorizas; N.S. Sadick (Wolters Kluwer, 2015)
Background: Skin cancer has reached epidemic proportions, with more new cases diagnosed annually than the combined incidence of cancers of the breast, prostate, lung, and colon. Estimates show 2 to 3 million new cases of non-melanoma skin cancer (NMSC) every year, and, among women, it is the young (younger than 45 years) who are disproportionately affected. Objective: This article aims to address questions and concerns pertinent to skin cancer in a woman-centric way. An updated landscape of causative factors, the latest detection/treatment methods, and ultimately the preventative measures available to them are described. Methods: A broad literature search was conducted using the PubMed database with search terms focusing on female gender. Additional articles were identified from cited references. Conclusions: The published findings on causation of melanoma skin cancer and non-melanoma skin cancer in females are outlined, as well as current detection methods and treatment options. Furthermore, a variety of preventative measures specific to women that can reduce the chance of being diagnosed with skin cancer are discussed.